The Effect of The Application of Organizational Allowance and Justice Policy on Financial Performance at The Central Lombok BPBD - Ikhwan Wadi; Suparlan Suparlan; Ahmad Murad; Asrin Asrin (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
This study aims to analyze the impact or influence of benefits and organizational justice policies on the financial performance of regional disaster management agencies in Lombok Regency. The sample in this study were all employees in the regional disaster management agency in Lombok Regency. The results showed that the application of the allowance policy had a positive and significant effect on financial performance in the regional disaster management agency in Central Lombok Regency, meaning that the allowance policy had a positive impact on improving financial performance. organizational justice has a positive and significant impact on the financial performance of regional disaster management agencies in Lombok Regency or organizational justice has a very positive impact on financial performance of regional disaster management agencies in Central Lombok Regency